2006
DOI: 10.1016/j.bbrc.2006.06.159
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK downregulates phosphorylation of Bad in doxorubicin-induced endothelial apoptosis

Abstract: Doxorubicin is the anthracycline with the widest spectrum of antitumor activity, and it has been shown that the antitumor activity is mediated in vivo by selective triggering of apoptosis in proliferating endothelial cells. We studied cultured human endothelial cells and observed that doxorubicin-induced apoptosis was mediated by p38 mitogen-activated protein kinase (MAPK). Doxorubicin-provoked apoptosis was significantly inhibited by expression of dominant negative p38 MAPK or pharmacological inhibition with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 52 publications
5
12
0
Order By: Relevance
“…Consistent with previous reports [18,24,26,27], we have also demonstrated that suppression of the activated p38α by either a pharmacological inhibitor (SB203580) or siRNA protects endothelial cells from apoptosis in response to growth factor withdrawal. The effect of TNF-α on cell survival in the presence or absence of p38 inhibitor, however, has been controversial.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with previous reports [18,24,26,27], we have also demonstrated that suppression of the activated p38α by either a pharmacological inhibitor (SB203580) or siRNA protects endothelial cells from apoptosis in response to growth factor withdrawal. The effect of TNF-α on cell survival in the presence or absence of p38 inhibitor, however, has been controversial.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with our findings, Bruening et al (20) reported that a p38 MAPK inhibitor completely blocked arsenite-induced up-regulation of the CMV promoter. Previous studies have shown that p38 MAPK is activated upon treatment with doxorubicin and paclitaxel (28,29). These studies also showed that inhibition of p38 MAPK reduced doxorubicin-and paclitaxel-induced apoptosis, demonstrating an important role for p38 MAPK in the apoptotic process.…”
Section: Discussionmentioning
confidence: 60%
“…However, the net biological effects on these cells are complex and variable. For example, under certain circumstances, TNF may induce EC apoptosis while at other times it may promote EC proliferation and angiogenesis (5,6). Some of this complexity may be explained by time-dependent alterations in signaling complexes.…”
Section: Tnfmentioning
confidence: 99%